IMPLEMENTASI PERATURAN GUBERNUR NOMOR 16 TAHUN 2019 TENTANG KAWASAN TANPA ROKOK DI KANTOR KEMENTERIAN AGRARIA DAN TATARUANG/BADAN PERTANAHAN NASIONAL (ATR/BPN) KUBU RAYA - WHIBOWO, FAISAL ADI; Maryuni, Sri; Triyono, Joko (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aimed to analyze what factors caused the non-optimal implementation of no-smoking area policy at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency Office of Kubu Raya Regency which was carried out by Public Order Enforcers of Kubu Raya as one of the implementers of the no-smoking area. This study used the qualitative descriptive research method. This study used Edward III’s implementation theory (in Winarno, 2014:177) which gave the view that policy implementation was influenced by four factors or variables, namely Communication, Resources, Bureaucratic Structure, and Disposition. The results showed that there was no socialization done yet by the agency related to the implementation of the no-smoking area policy, the human resources were not sufficient to implement policies and policy support facilities were not yet available, the bureaucratic structure was in accordance with the applicable regulations, and there was no commitment from policy implementers to actualize this no-smoking area policy. The researcher suggests that the socialization must continue to be carried out to reduce the level of policy violations and increase public awareness to comply with regulations, the researcher also suggests to apply strict sanctions that are indiscriminate and increase human resources so that policy implementation can be carried out optimally.Keywords: Implementation, Policy, Communication, Sanction.